Experimental investigation of organic Rankine cycle performance using alkanes or hexamethyldisiloxane as a working fluid - Khider Abbas Abbas, Wameedh; Baumhögger, Elmar; Vrabec, Jadran (Energy Conversion and Management: X)
Keywords: Energy Engineering and Power Technology; Fuel Technology; Nuclear Energy and Engineering; Renewable Energy; Sustainability and the Environment

Thermodynamic Properties for 1-Hexene – Measurements and Modeling - Betken, Benjamin; Beckmüller, Robin; Ali Javed, Muhammad; Baumhögger, Elmar; Span, Roland; Vrabec, Jadran; Thol, Monika (The Journal of Chemical Thermodynamics)
Keywords: Physical and Theoretical Chemistry; General Materials Science; Atomic and Molecular Physics; and Optics

Development of a Numerical 3D Model for Analyzing Clinched Joints in Versatile Process Chains - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (The Minerals, Metals & Materials Series)
The application of the mechanical joining process clinching enables the joining of sheet metals with a wide range of material-thickness configurations, which is of interest in lightweight construction of multi-material structures. Each material-thickness combination results in a joint with its own property profile that is affected differently by variations. Manufacturing process-related effects from preforming steps influence the geometric shape of a clinched joint as well as its load-bearing capacity. During the clinching process high degrees of plastic strain, increased temperatures and high strain rates occur. In this context, a 3D numerical model was developed which can represent the material-specific behaviour during the process chain steps sheet metal forming, joining, and loading phase in order to achieve a high predictive accuracy of the simulation. Besides to the investigation of the prediction accuracy, the extent of the influence of individual modelling aspects such as temperature and strain rate dependency is examined.

Out of the Box and into the Gutter. Rethinking Space in Michael Nicoll Yahgulanaas' Haida Manga Art - Jende, Yvonne Kristin (Artistic Practices of (Un-)Making Place, International and Interdisciplinary Conference)

Multidomänensimulation des Schaltverhaltens von Federkraftbremsen - Blumenthal, Lars Martin; Zimmer, Detmar (Konstruktion)
Simulationen können Entwicklungsprozesse für individualisierte Federkraftbremsen zielgerichtet unterstützen. Die Herausforderung besteht dabei in der Vielzahl der unterschiedlichen physikalischen Effekte, die in Federkraftbremsen miteinander in Wechselwirkung stehen. Dieser Artikel beschreibt einen Ansatz für die Simulation des Schaltverhaltens von Federkraftbremsen unter Berücksichtigung der Elektrizität, des Magnetismus, der Mechanik, der Thermodynamik und der Thermodilatation in einem gemeinsamen Modell. Eine experimentelle Validierung weist die Gültigkeit des Modells nach.
Keywords: Mechanical Engineering

Analysis of Differential Algebraic Equation Systems for Connecting Energy Storages of Generally Valid Functional Mock-up Units - Ehlert, Meik; Henke, Christian; Trächtler, Ansgar (Proceedings of the 12th International Conference on Simulation and Modeling Methodologies, Technologies and Applications)

Konzept für ein hierarchisches autonomes Verkehrsmanagement - Mertin, Sven

Innovative assistance system for setting up a mechatronic straightening machine - Bathelt, Lukas; Bader, Fabian; Djakow, Eugen; Henke, Christian; Trächtler, Ansgar; Homberg, Werner
High-strength wire materials are usually available as strip material which is further processed in a forming process (e.g. punch-bending). For storage and transport of the semi-finished wire to the customer, the material is wound onto coils. The manufacturing and coiling process introduces plastic deformations into the wire, which lead to undesirable residual stresses and wire curvature of the semi-finished product. These residual stresses and curvatures cause variations in the material properties of the semi-finished product, which have a negative impact on the subsequent product quality. Straightening machines are used to compensate the residual stresses and the curvature in the wire. At the beginning of the straightening process, the straightening machines must be set up in such a way that residual stresses and curvatures are optimally compensated. This setup process is usually a manual and iterative process, where a lot of material is wasted until the optimal settings for the straightening machine are found.In order to reduce the amount of material waste, the operator must be supported in the setup process. In this context, a new and innovative setup assistance system was developed to support the operator during the setup process. The setup assistant system automatically detects the wire curvature by means of an optical measuring system. Based on the optically detected measuring points, the wire curvature is determined by a robust calculation algorithm. Based on a database built up through the carried out experimental and numerical research work, the optimum setting parameters for the straightening machine are suggested to the operator without lengthy trial and error. After confirmation by the operator, the roller settings are automatically adjusted by the mechatronic straightening machine. With the presented method, the conventional iterative setup procedure can be made more resource-efficient and a high straightening quality can be reproducibly achieved.

An approach for an innovative 3d steel strip straightening machine for curvature and saber compensation - Bader, Fabian; Bathelt, Lukas; Djakow, Eugen; Henke, Christian; Homberg, Werner; Trächtler, Ansgar
Due to increasing globalization and rising quality requirements, the steel and metal processing industry is facing growing cost and innovation pressure. Not least because of their high lightweight potential, high-strength steel materials are meeting the growing material requirements of steel and metal processing in areas such as aerospace and medical technology. In particular, the tight tolerance limits of applicable shape and dimensional accuracies pose a challenge in the processing of high-strength steel strip materials. Improving the processability of high-strength steel materials through the use of straighteners with set-up assistance systems significantly increases the potential for competing with other materials such as aluminum or magnesium alloys.

Tool Wear Monitoring of a Tree Log Bandsaw using a Deep Convolutional Neural Network on challenging data - Koppert, Steven; Henke, Christian; Trächtler, Ansgar; Möhringer, Stefan (IFAC-PapersOnLine)
Keywords: Control and Systems Engineering

Data-Driven Adaptive Torque Oscillation Compensation for Multi-Motor Drive Systems - Brosch, Anian; Rauhaus, Johann; Wallscheid, Oliver; Böcker, Joachim; Zimmer, Detmar (IEEE Open Journal of Industry Applications)

Mechatronische Richtapparate: Intelligente Richttechnik von hochfesten Flachdrähten - Bathelt, Lukas; Bader, Fabian; Djakow, Eugen; Henke, Christian; Trächtler, Ansgar; Homberg, Werner (Fachtagung VDI MECHATRONIK 2022)

Virtual Commissioning of the Trajectory Tracking Control of a Sensor-Guided, Kinematically Redundant Robotic Welding System on a PLC - Schütz, Stefan; Schmidt, Robin; Henke, Christian; Trächtler, Ansgar (2022 IEEE International Systems Conference (SysCon))

Anomaly Detection in Hot Forming Processes using Hybrid Modeling - Part II - Lenz, Cederic; Hanke, Fabian; Henke, Christian; Trächtler, Ansgar (2022 27th IEEE International Conference on Emerging Technologies and Factory Automation (ETFA ))

Untersuchung und Entwicklung eines modularen speicherbasierten Schweißstromgenerators mit geringster Stromschwankungsbreite für das Widerstandsschweißen - Hagemeyer, Marc

MECHANICALLY JOINED EXTRUSION PROFILES FOR BATTERY TRAYS - Neumann, Stefan; Meschut, Gerson; Otroshi, Mortaza; Kneuper, Florian; Schulze, Andre; Tekkaya, Erman

A PLIC-based method for species mass transfer at free fluid interfaces - Schulz, Andreas Markus; Wecker, Christian; Inguva, Venkatesh; Lopatin, Alexey S.; Kenig, Eugeny Y. (Chemical Engineering Science)

Droplet formation –a numerical investigation of liquid-liquid systems with consideration of Marangoni convection - Wecker, Christian; Schulz, Andreas Markus; Heine, Jens; Bart, Hans Jörg; Kenig, Eugeny Y. (International Journal of Heat and Mass Transfer)

Experimentelle Untersuchung der Tropfenkondensation am chemisch modifizierten Edelstahl‐Drallrohr - Dai, Daokun; Kenig, Eugeny Y.; Numrich, Reiner (Chemie Ingenieur Technik)
Keywords: Industrial and Manufacturing Engineering; General Chemical Engineering; General Chemistry

A front-tracking method for two-phase flow simulation with no spurious currents - Inguva, Venkatesh; Kenig, Eugeny Y.; Perot, J. Blair (Journal of Computational Physics)